Real world reflection: how physiotherapists experience reflection in their practice. Issue 1 (2nd January 2023) - Dalley-Hewer, Jayne; Clouder, D.L.; Jones, M.
ABSTRACT: This paper explores the nature of reflection that qualified physiotherapists use in their day-to-day practice. This is an area in which there is a dearth of research. With a grounded theory approach purposive sampling was used to recruit seven qualified physiotherapists for photo-elicitation interviews exploring whether they did reflect and if so, what their reflection was like. The findings were that they did reflect but that it occurred outside of working hours. Four conceptual categories were identified: Personal Concept, Personal Process, Time and Head-Space. Practitioners had their own ideas of what reflection was, own ways of reflecting and personal strategies for making the head space to reflect in. Typically, they used thinking modes of reflection, with occasional dialogical modes; written reflection was rare. Of novel significance was the use of strategies to complete reflection to their satisfaction, most frequently walking but also preparing vegetables, driving and showering, typically outside of work hours. The use of such cognitively non-demanding, routinised activities to aid reflection has not been widely explored in the literature on reflection and may suggest a need to rethink approaches to support the teaching of reflection which would have high validity for its place in the real world of practice.